The Phenomenon of Counselor Career Satisfaction in View from the Perspective of Dual Factor Theory: Systematic Literature Review - Guspriadi, Yan; Afdal, Afdal; Hariko, Rezki; Yunus, Ahmad Rozelan; Ardi, Zadrian (Psikopedagogia, 2023)
In the face of the substantial impact of the COVID-19 epidemic, Industry 4.0 has expedited innovation in several industries, including education. The objective of this study is to investigate the impact of intrinsic and extrinsic influences on the job satisfaction of counselors by applying Herzberg's dual factor theory. The employed methodology is a systematic literature review, encompassing the stages of identification, screening, eligibility, data abstraction, and analysis. This study examined scholarly papers published between 2019 and 2023, with a specific focus on school counselors and the field of guidance education. After applying rigorous inclusion and exclusion criteria, the selection procedure yielded 10 pertinent articles out of 378 discovered documents. The study findings suggest that motivating circumstances, such as professional recognition, achievement, and development possibilities, have a substantial impact on the job satisfaction of counselors. By contrast, job discontent and burnout are linked to hygienic variables such as an excessive workload and insufficient institutional assistance. The present study highlights the necessity of achieving a harmonious equilibrium between motivators and hygienic elements in order to enhance the psychological well-being and job satisfaction of counselors. The results of this study offer valuable perspectives for the formulation of policies and implementation of strategies that promote the well-being of counselors in educational environments.